Some Peculiarities of Low-Frequency Hydroacoustic Signals Behavior in Tomographic Studies of “Sea-Land-Sea” System - Sergey Budrin; Grigory Dolgikh; Vladimir Chupin; Stanislav Dolgikh (Journal of Marine Science and Engineering, 2022)
In this paper, we analyzed the results of experimental data processing in the study of regularities of propagation and transformation of low-frequency harmonic signals at the boundary of the “sea−land−sea” system. Harmonic signals at a carrier frequency of 33 Hz were generated by a low-frequency hydroacoustic radiator in Vityaz Bay. Then, they passed along the shelf of decreasing depth, transformed into seismoacoustic signals of the upper layer of the Earth’s crust and the bedrocks of Shultz Cape and excited hydroacoustic signals at the corresponding frequency in the shelf waters in the open part of the Sea of Japan. When processing the experiment results, we obtained the vertical distributions of the pressure field, caused by an acoustic low-frequency signal passing through the upper layer of the Earth’s crust. We presented the distributions of hydroacoustic and seismoacoustic energies. The obtained experimental data were compared with the simulations by the model, developed strictly according to the experiment scheme and the geological structure of the area. In the discussion of the obtained results, we explained a probable mechanism of acoustic energy propagation and the nature of the vertical distributions of the pressure field formation.